Contradições do PRONAF : fortalecimento ou manutenção da submissão da agricultura camponesa em assentamentos de reforma agrária no alto sertão sergipano? - Melo, Alvanira Ribeiro (2010)
The politics of rural credit in Brazil have long favored the large and medium landowners with highly subsidized credits for the purpose of strengthening export monoculture and agro-industry. The social consequences of so-called conservative modernization of the Brazilian society were disastrous, a large contingent of rural workers were dispossessed of their land, while those who resisted competed on an unequal credit policies. With the increase of poverty and social inequality in the country, workers have been mobilized in the struggle for agrarian reform and better living conditions for the population. In response to claims and following the guidelines of the World Bank for agricultural policy of the country in mid-1990 there is a paradigm shift regarding the policies of rural credit. Thus was created the National Program for Strengthening Family Agriculture - PRONAF. Among the main objectives of the program are: the generation of employment and income, improved living conditions and integration of small farmers in the market. In 1999 farmers were entered into politics through the "A" line. Our study aimed to analyze whether the inclusion in the program allowed farmers included in land reform projects has enabled an improved in their living conditions. The empirical research were cut out of our settlements Cuyabá and Pioneira, located in the district of Canindé the São Francisco and Poço Redondo, both belonging to the territory of the high backwoods of Sergipe.